Timing parameters of Pyrotechnic Igniter based on Magnesium powder - Pelikán, Vojtěch; Kuracina, Richard; Szabová, Zuzana (Sciendo, 2019)
Chemical igniters are used in the study of dispersed dusts. Energy released during their use is defined by EN 14034 at 2 x 5 kJ. The Standard does not define the exact composition of the pyrotechnic mixture. The condition of using the igniter is to release energy according to the Standard. This article is focused on pyrotechnic composition with magnesium powder. It deals with various ways of activating, preparing and sealing the pyrotechnic mixture in the igniter. These values are important for setting up a device for studying the explosive properties of dispersed dusts.
Časování pyrotechnického zažehovače obsahem práškového hořčíku
Keywords: Igniter; Zažehovač; chemický zažehovač; prachová disperze; hořčíkový prášek; chemical igniter; dispersed dust; magnesium powder